Longitudinal shear resistance of PVA-ECC composite slabs - Mohammed, B.S. (Elsevier Ltd, 2016)
Including polyvinyl alcohol (PVA) fiber to develop a ductile engineered cementitious composite (ECC) is an effective way to overcome the brittle behavior of conventional concrete and to increase the efficiency of composite slab construction. Two groups of full-scale composite slabs were prepared, cast and tested until failure. Each group consists of three PVA-ECC composite slabs and one control specimen made with normal concrete topping. The first group has been tested with long shear span of 900 mm while for the second group, the shear span was 450 mm. Test results have been analyzed and the longitudinal shear bond strength has been computed using both methods of m-k and partial shear connection (PSC). In addition, comparison with other types of composite slabs using the same profiled steel sheeting was also carried out. The longitudinal shear bond strength was found to be 0.46 MPa and 0.387 MPa using m-k and PSC, respectively, with difference of 15.87. The results showed that the failure modes of the PVA-ECC composite slabs are ductile with enhanced load carrying capacity. Therefore the use of PVA-ECC composite slabs in the construction industry would consider a better economic solution. Â© 2015 Elsevier B.V.